Design of Microstrip Patch Antenna with Quarter Wave Transformer for Ism Band - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents a design of microstrip patch antenna with quarter wave transformer for ISM Band. The antenna is designed over the operating frequency is 2.4 GHz using the substrate material as FR-4. The designed antenna can be used for ISM (industrial, scientific and medical) band applications in Wireless Body Area Networks (WBAN). Different performance parameters of the antenna such as operating frequency, Return Loss, Voltage Standing Wave Ratio (VSWR), directivity, SAR have been analyzed both in planar conditions on the human tissue model by using CST Microwave Studio. Finally, Specific Absorption Rate (SAR) is evaluated to satisfy the antenna safety concern on the human body. © 2019 IEEE.